2012
DOI: 10.1093/infdis/jis726
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neuraminidase Inhibitor Treatment on Outcomes of Public Health Importance During the 2009-2010 Influenza A(H1N1) Pandemic: A Systematic Review and Meta-Analysis in Hospitalized Patients

Abstract: Background. The impact of neuraminidase inhibitor (NAI) treatment on clinical outcomes of public health importance during the 2009–2010 pandemic has not been firmly established.Methods. We conducted a systematic review and meta-analysis, searching 11 databases (2009 through April 2012) for relevant studies. We used standard methods conforming to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were estimated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
109
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(120 citation statements)
references
References 23 publications
7
109
0
4
Order By: Relevance
“…To our knowledge, there have been five deaths in comparative Phase II/III RCTs of oseltamivir; 167,168 however, none of the deaths was in a patient with confirmed influenza. Reviews of observational studies of influenza 2009A/H1N1 have shown protective effects of NIs on mortality [169][170][171][172][173] and oseltamivir is now listed as an essential medicine, 174 although there is insufficient evidence based on randomised studies to show that oseltamivir reduces complications of influenza 106 and case series have suggested increased mortality. 15,141 The objective of this systematic review was to determine the effect of oseltamivir treatment on mortality in patients with 2009A/H1N1 influenza.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there have been five deaths in comparative Phase II/III RCTs of oseltamivir; 167,168 however, none of the deaths was in a patient with confirmed influenza. Reviews of observational studies of influenza 2009A/H1N1 have shown protective effects of NIs on mortality [169][170][171][172][173] and oseltamivir is now listed as an essential medicine, 174 although there is insufficient evidence based on randomised studies to show that oseltamivir reduces complications of influenza 106 and case series have suggested increased mortality. 15,141 The objective of this systematic review was to determine the effect of oseltamivir treatment on mortality in patients with 2009A/H1N1 influenza.…”
Section: Introductionmentioning
confidence: 99%
“…There are also a number of published observational studies providing data that support the efficacy of NIs (oral oseltamivir, inhaled zanamivir) for uncomplicated influenza, reducing fever and illness duration by approximately one day [51,52]. NIs have also been found to be effective in reducing mortality in patients hospitalized with pH1N1 virus infection including, but not limited to, pregnant women [50,53].…”
Section: Treatmentmentioning
confidence: 99%
“…Sudden death is another concern [5-7]. A causal association between oseltamivir use and abnormal behaviours or sudden death has not been established and it is considered negative [1,2] based on retrospective observational studies [8-12], systematic reviews of retrospective observational studies [13,14] and a systematic review and meta-analysis of randomized controlled trials of oseltamivir treatment for influenza of adults [15]. …”
Section: Introductionmentioning
confidence: 99%